Social and human sciences in the Orinoquia and the Amazon (2020)
The interdisciplinary collection Studies of the Orinoquia and the Amazon seeks to generate knowledge, encourage academic discussion and assume alternative solutions to regional problems in the Orinoquia and the Amazon. If the Orinoquia and the Amazon are special territories due to their historical abandonment and they constitute a unique region, they must have a special treatment that facilitates their development and promotes access to scientific knowledge and goods produced in the developed world with respect for populations ancestral and regional cultures. In this second volume are works related to social and human sciences in these regions. Topics ranging from education in the Orinoquia are addressed; geopolitics, physical integration and development in the Amazon; passing through the quilombolas collectives in the Brazilian Amazon; contemporary Amazonian painting; indigenous life plans of the Amazon and Orinoquia; until the study of myth, the market and multiple ontologies in a forest garden project among the Sateré-Mawé of the Brazilian Amazon. The themes are varied and must be assumed from a theoretical, methodological and procedural opening to reach an understanding of the phenomenon in its dimensions and its contexts.